Evaluating the role of hemogram based parameters in febrile seizures - Rao, Aarathi; Aroor , Amitha Rao (International Journal of Research in Medical Sciences, 2024)
Background: One of the most common childhood neurological disorders is febrile seizures (FS). Parents may have trouble describing the events pertaining to seizures, which might lead to aberrations in the diagnosis and classification of FS. Hence, objective biomarkers to predict and classify FS will be clinically beneficial. The aim of this study was to evaluate role of hemogram based parameters (NLR, PLR, RDW, MPV) in the outcome of children with febrile seizures (FSs) and in differentiating between simple and complex febrile seizures. Methods: A total of 50 patients with FSs (group A) who were hospitalized in our hospital were selected. Fifty patients with fever and without seizures (group B). The results of hemogram were collected retrospectively and analysed. Results: The hemogram analysis showed that hemoglobin (Hb) in group A was significantly lower than in the group B (p<0.05). The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), MPV and RDW in group A was significantly higher than in group B. The MPV and NLR values in the CFS group was higher in comparison to SFS group (p<0.05). Conclusions: As statistically significant differences were found in the hemogram parameters like HB, RDW, MPV, NLR PLR between febrile seizure group and non-febrile seizure group, these parameters can aid in diagnosing the same. High NLR and MPV levels may be able to serve as simple yet effective laboratory indicator for distinguishing between simple and complex febrile seizures.